Meeting (or not) at the street level? A literature review on street‐level research in public management, social policy and social work. (19th January 2018) - Nothdurfter, Urban; Hermans, Koen
Abstract : This literature review analyses the adoption and development of a street‐level perspective in public management, social policy and social work. The last years have seen a prominent revival of a perspective based on Michael Lipsky's street‐level bureaucracy approach in the debates conducted within all three disciplinary fields. Based on 71 key publications in public management, social policy and social work, the review analyses the adoption of the street‐level bureaucracy approach during the period 2005–2015, pointing out the main themes of the debate within, as well as overlaps and differences between, the three disciplines. The findings show the potential of better integrating the different perspectives and taking stock of the articulated debate. Lastly, the review discerns a common viewpoint for further street‐level research, emphasising its importance for the critical analysis and understanding of street‐level work as a vital dimension of responsive and accountable institutions and as a decisive moment to shape positive policy outcomes on the ground. Key Practitioner Message: The use of discretion by frontline practitioners and their role as policy actors on the ground has become an important focus of research; This literature review shows that the debate has gone far beyond discussing discretion as an all‐or‐nothing issue, pointing out both positive and negative aspects of discretion and developing comprehensive frameworks to explain the use of discretion at the street‐level; However, street‐level research has traditionally rather neglected the notion of professionalism. The social work literature brings in the perspective of professionalism; more research efforts are needed to better explore and explain how professionalism matters in relation to challenges and dilemmas of different policy and practice fields.